(untitled) (Nexus International Journal of Science and Education, 2024)
This qualitative study offered an in-depth exploration of the authentic narratives of secondary school teachers in Talaingod, Davao del Norte, Shed light on the complex challenges they encounter in their profession, particularly regarding burnout. The research uncovered the nuanced factors contributing to educators' work burnout through extensive interviews and analysis. The identified stressors were heavy workloads, inadequate support systems, and classroom management strategies. In response to these challenges, teachers employed various coping mechanisms, from attending spiritual upliftment, building professional networks, and joining professional training opportunities. The study underscored the importance of these coping strategies in navigating the profession's demands. It highlighted the educational management insights observed in discussions as the pivotal role of self-reflection and seeking support systems in maintaining resilience. Furthermore, it emphasized creating a supportive and healthy school environment that prioritizes teacher well-being and fosters a culture of collaboration, empathy, and mutual support. By addressing these issues, the well-being and satisfaction of teachers can be enhanced, and the school community's overall effectiveness and positive impact can also be significantly strengthened. The advocacy for embedding networking into teacher well-being efforts encourages institutions to acknowledge its positive influence.